Making Undergraduate Research a Central Strategy in High‐Impact Practice Reform: The PASSHE Journey. Issue 169 (March 2015) - Moran III, James D.; Wells, Marilyn J.; Smith‐Aumen, Angela
Abstract : This chapter describes undergraduate research expansion in the Pennsylvania State System of Higher Education (PASSHE) in the context of both fiscal and student enrollment challenges.